TEACHERS’ PERCEPTION ON SCHOOL HEAD’S LEADERSHIP PRACTICES IN ADDRESSING INFRASTRUCTURE AND FACILITIES CHALLENGES - Olga C. Alonsabe; Michael Vincent S. Casino; Michelle L. Mamburao; Therese Angeli M. Romasanta (Galaxy International Interdisciplinary Research Journal, 2024)
Infrastructure and facilities serve as essential instructional resources that must be competently maintained and are an integral aspect of educational administration. This study explores teachers’ perceptions of school head leadership practices in addressing infrastructure and facilities challenges among the teachers of Region X, Northern Mindanao. Through a comprehensive survey, the research reveals a generally positive impression of the school head’s leadership in managing infrastructure concerns. However, despite positive leadership perceptions, the study highlights significant worries among teachers regarding insufficient infrastructure, particularly in terms of classroom space, technology, laboratories, and overall safety and accessibility. The study emphasizes the alignment of infrastructure and facilities projects with teacher goals, and foster a cooperative and supportive learning environment.